Igbo women in the diaspora and community development in southeastern Nigeria : gender, migration, and development in Africa - Aham-Okoro, Sussie U. (Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2017)
This book examines the role that Igbo women in the diaspora play in community development in Southeastern Nigeria. It provides recommendations to policy makers in engaging and integrating diaspora resources to community development processes in Africa.